THE ROLE OF ACADEMIC SUPERVISORS IN IMPROVING STUDENT LEARNING ACHIEVEMENT - Ninies Eryadini (Jurnal Scientia, 2022)
This study aims to describe the roles and functions of Academic Advisors in providing guidance services to students. In attending college, students often experience problems that need help in dealing with these problems, which are not only academic problems such as preparing KRS, but also problems allocating time, participation in lectures and even problems that are personal or non-academic in nature. This research uses a descriptive method with a qualitative approach. Data collection is done through observation, interviews and documentation. The results of the study show that the role of Academic Advisors is very strategic in helping students during lectures. The main task of the Academic Advisor is to act as an informant, facilitator, motivator and supervisor for students.